2021
DOI: 10.1080/10402004.2021.1943088
|View full text |Cite
|
Sign up to set email alerts
|

An Evaporation Model for Base Oil from Grease-Lubricated Rolling Bearings including Breathing

Abstract: The film thickness decay of grease lubricated bearings is determined by a loss of lubricant from the bearing. One of these loss mechanisms is base oil evaporation. In this paper, a model is presented for evaporation where the volatiles leave the bearing by breathing. The model is applied to a typical drive cycle where the temperature is varied in time. With the model, the impact of the volatility of base oils and quality of sealing on the evaporation losses can be quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…It is important to mention that evaporation of lubricants can have an influence on the results of the Turbin Oxidation Stability Test Method [27]. According to the manufacturer, no volatile oil components are part of the lubricant's formulation in the first place.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to mention that evaporation of lubricants can have an influence on the results of the Turbin Oxidation Stability Test Method [27]. According to the manufacturer, no volatile oil components are part of the lubricant's formulation in the first place.…”
Section: Methodsmentioning
confidence: 99%
“…The mass loss caused by the loss of volatiles could have been accelerated by the air/N 2 flow though the bearing. After all, our earlier study on the impact of base oil evaporation on mass loss showed that this was very small [46]. To investigate this, the impact of this air flow on grease life, also a test without air flow was done and the result was identical.…”
Section: Leakage Versus Mass Lossmentioning
confidence: 97%